1978
DOI: 10.1007/bf03350382
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptors in human fetal lung

Abstract: A specific dexamethasone binding protein of human fetal lung is described. Characterization of the receptor by sucrose density gradient centrifugation showed a sedimentation coefficient of approximately 7S (low ionic strength) and 4S (high ionic strength). Competition studies showed high specificity for glucocorticoids since binding of radioactive dexamethasone was inhibited by cortisol and corticosterone but not by testosterone and 17 beta-estradiol. Uptake of radioactive steroid by isolated lung nuclei requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Hydrocortisone being a good competitor (Table 2), the dexamethasone binder could not be an aldosterone receptor. The sedimentation pattern is in the same order of magitude as found by other workers [4,7,11]. As mentioned above, Giannopoulos [7] was not able to detect a glucocorticoid receptor in adult human lung [4].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Hydrocortisone being a good competitor (Table 2), the dexamethasone binder could not be an aldosterone receptor. The sedimentation pattern is in the same order of magitude as found by other workers [4,7,11]. As mentioned above, Giannopoulos [7] was not able to detect a glucocorticoid receptor in adult human lung [4].…”
Section: Discussionsupporting
confidence: 71%
“…The apparent dissociation constant (5.8-21.0nM) is within the range of magnitude as those reported for other human glucocorticoid target tissues (adult liver: 1.7 nM [5], mammary carcinoma: 4.4-9.4 nM [20], malignant melanoma: 2-22 nM [4], fetal lung: 7.1 nM [11], A-549 cell line: 7.1 nM [12], human alveolar macrophages: 9.79 nM [17]. The glucocorticoid receptor content (mean+ S.D.…”
Section: Discussionmentioning
confidence: 73%
“…Ballard and Ballard reported that in the cytosol of lung tissue the GR concentration ranged from 40 to 350fmoYmg protein, in tissue obtained at autopsy from foetuses of 12-43 weeks of gestational age (3). Similar results (17) or lower GR concentrations (between 70 and 180 fmol/mg protein) (4) and between 1 1 0 and 300fmol/mg protein (5.1 were reported. The GR number in foetal lung tissue is independent of gestational age (3.…”
Section: Discussionmentioning
confidence: 71%
“…Ozaki et a1.15 measured these receptors in bronchoalveolar cells obtained by lavage for the same indication of diffuse interstitial fibrosis. Receptor concentration was 5,581 2 3,741 sitedcells in cases of diffuse interstitial fibrosis and 9,970 & 4,052 sites/cells in healthy individuals. Bad responders to glucocorticoid treatment had the lowest receptor levels.…”
Section: Discussionmentioning
confidence: 93%